Preliminary analysis of the correlation between BMI and human psychological condition using energy field interpretation. / Norhazlina Harun - Harun, Norhazlina
This technical paper analyzes the correlation of body mass index (BMI) and human's psychological condition using energy field interpretation. Frequency measurement is taken from 40 students including male and female students with different BMI categories. The analysis were categorized in four parts which are poor, moderate, good and excellent emotional health. This is to see the relation of different psychological condition with BMI category such as underweight, normal, overweight and obese. Based on the results presented, it can be said that all the samples in general have moderate mental or emotional health except for the samples with normal BMI. Samples with normal BMI show overall good mental or emotional health. The findings show that samples that are obese have the highest tendency to have poor psychological health. Person with good emotional health are aware of their thoughts, feelings and behaviors. They have learned healthy ways to cope with the stress and problems that are a normal part of life. They also feel good about themselves and have healthy relationships. It also implies that taking care of our body is a powerful first step towards mental and emotional health.